Highly Efficient Metasurface Polarization Converter at Far-Infrared Range - Tamim, Ahmed Mahfuz; Hasan, Md Mehedi; Faruque, Mohammad Rashed Iqbal (Frontiers in Physics, 2022)
Controlling the polarisation state is an efficient way to enhance the functionalities in sensing, imaging and communication systems in the microwave and terahertz (THz) spectrum. This study proposed an anisotropic metasurface and numerically explained it as a highly efficient polarisation conversion using far-infrared frequency. Structural design, optimisation, and results examination of the metasurface are performed using the CST microwave studio electromagnetic simulator. The metasurface was developed surrounding the two individual arrow-shaped metal resonators with two bar resonators on the opposite angular side of the arrow. Aluminium (Al) was used as a metallic resonator, while gallium arsenide (GaAs) as the substrate. The interference theory was used to describe the co-polarised and cross-polarised reflectance coefficients, where two different mediums and interference layers were considered along with the reflected and transmitted wave. The polarisation conversion efficiency yielded over 90% from 282.9 to 302.3 µm (0.987 – 1.062 THz) and 558.78 to 676.7 µm (0.442 – 0.537 THz) indicating multiple resonances at 286.7 µm, 298.25 µm, 586.1 µm, and 689.55 µm. In conclusion, the performances and diverse characteristics of the designed metasurface demonstrated potential applications in the far-infrared spectrum as an efficient polarisation converter application.